Hacking cell differentiation: transcriptional rerouting in reprogramming, lineage infidelity and metaplasia. Issue 8 (4th July 2013) - Regalo, Gonçalo; Leutz, Achim
<x xml:space="preserve">Abstract</x> Initiating neoplastic cell transformation events are of paramount importance for the comprehension of regeneration and vanguard oncogenic processes but are difficult to characterize and frequently clinically overlooked. In epithelia, pre‐neoplastic transformation stages are often distinguished by the appearance of phenotypic features of another differentiated tissue, termed metaplasia. In haemato/lymphopoietic malignancies, cell lineage ambiguity is increasingly recorded. Both, metaplasia and biphenotypic leukaemia/lymphoma represent examples of dysregulated cell differentiation that reflect a history of trans‐differentiation and/or epigenetic reprogramming. Here we compare the similarity between molecular events of experimental cell trans‐differentiation as an emerging therapeutic concept, with lineage confusion, as in metaplasia and dysplasia forecasting tumour development.